ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SD NEGERI 40 AMBON PADA MATERI BANGUN DATAR - T, Rachmawati; Laurens, Theresia; Moma, La (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2019)
The purpose of this study was to determine the mathematical creative thinking ability of Grade VI students of SD Negeri 40 Ambon on flat material. This type of research is a descriptive study with a qualitative approach. The subjects in this study were fifth grade students of SD Negeri 40 Ambon in semester 2 of 2018/2019 academic year as many as five people. The subject taking technique is done by purposive sampling. Methods of data collection through tests of mathematical creative thinking and interviews. Data analysis techniques refer to the opinion of Miles and L-Luberman, namely the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results showed that the five subjects representing each level of creative thinking ability had different characters in showing indicators of creative thinking ability